Information system and business governance in the Politeknik Negeri Medan business unit - Fachrizal, Ferry; Kamil, Idham; Ginting, Jasa; Hutagalung, Gabriel Ardi (Institute of Computer Science (IOCS), 2025)
Politeknik Negeri Medan (Polmed) has various business units that support academic and non-academic activities. However, performance management and business governance of these units face various challenges, especially due to the use of manual and non-integrated systems. The main problems faced include inaccurate data, information delays, difficulties in monitoring and evaluation, and inefficient document management. This research aims to develop an integrated Performance and Business Governance Information System to collect data, manage and present business reports in the Polmed business unit. This system is expected to increase the accuracy and speed of data processing, facilitate access and presentation of information for management, and increase efficiency in monitoring and evaluating business unit performance. Apart from that, this system is also expected to optimize the management of business documents and reports. Through a research and development (R&D) approach, this system was designed and implemented by utilizing the latest information technology. The research results show that the implementation of this information system is able to overcome various existing problems, as well as support improved performance and governance of the Polmed business unit. Thus, this research makes a significant contribution in supporting the vision and mission of Polmed as a superior educational institution.